O ovirah v integracijskem procesu priseljencev v Mariboru - Marič, Mojca (Studia Historica Slovenica, 2025)
This article investigates how immigrants in Maribor, Slovenia, understand the circumstances of their migration, the motivations behind it, and how they assess their lives and integration into Slovene society. Drawing on anthropological f ieldwork and a detailed analysis of three semi-structured interviews – conducted respectively with a refugee, an economic migrant, and a love migrant – the study presents immigrants' perceptions of the integration process and identifies the key obstacles they consistently describe, despite their diverse backgrounds. These shared challenges concern linguistic integration, economic integration and employment, social integration, access to essential information, and experiences of discrimination, including both biological and cultural forms of racism.
Keywords: cultural anthropology; integracija; integration; kanonizacijamigracije; kulturna antropologija; migrations; postsocialism; postsocializem; Slovenia; Slovenija; social anthropology; socialna antropologija